PO.1.8 Distinct transcriptomic signature of peripheral blood in neuropsychiatric lupus. (27th September 2022) - Nikolopoulos, D; Filia, A; Katsiki, K; Manolakou, T; Pieta, A; Kapsala, N; Bertsias, G; Fanouriakis, A; Boumpas, D
Abstract : Purpose: We sought to identify distinct blood transcriptomic signatures of NPSLE patients that could serve as potential biomarkers and therapeutic targets. Methods: NPSLE was defined as patients with primary neuropsychiatric events (attributed to SLE) using a combination of multidisciplinary physician judgment with attribution models. Patients without neuropsychiatric events or secondary NPSLE (neuropsychiatric manifestations not attributed to SLE) were classified as non-NPSLE. Diagnosis of SLE was established by the Systemic Lupus Erythematosus International Collaborating Clinics (SLICC) 2012 criteria. RNA-sequencing was performed in peripheral blood from 172 individuals (54 NPSLE, 94 non-NPSLE and 24 healthy controls). Relative expression levels of transcripts and differentially expressed genes (DEGs) (FC >1.5, FDR <0.2) were calculated. Gene set enrichment analysis (GSEA; Preranked) and Gene ontology (GO; gprofiler) analyses were performed in RNA datasets. Results: Comparison of NPSLE with healthy controls revealed 103 DEGs mainly involved in inflammatory pathways (leukocyte cell-cell adhesion, regulation of leukocyte proliferation, neutrophil aggregation, complement and coagulation cascades, Toll-like receptor binding, NF-kappa B signaling pathway) suggesting that systemic inflammation is a key component in NPSLE pathogenesis. Comparison of NPSLE with non-NPSLE patients by GSEA analysis (FDR<0.25) revealed angiogenesis (FGFR1, LPL, PGLYRP1), complement (C3, ITGAM, CASP7), coagulation (VWF, ADAM9, CAPN2) G2M checkpoint (CHEK1, MKI67, CDKN3), MYC targets (XRCC6, PCNA, ILF2), E2F targets (CDK1, CKS1B, SMC3), estrogen response (MYB, CKB, SLC1A4), neutrophil degranulation (TNFAIP6, MMP8, LCN2) and PPAR signaling pathway (DBI, LPL, FABP5) being significantly enriched in NPSLE. Conclusions: NPSLE patients exhibit distinct transcriptomic signature compared to SLE patients without NP events. These data could facilitate the development of novel biomarkers and therapeutic targets. Acknowledgments: The European Research Council (ERC) under the European Union's Horizon 2020 research and innovation programme (grant agreement no.742390); and the SYSCID (A Systems Medicine Approach to Chronic Inflammatory Diseases) under the European Union's Horizon 2020 research and innovation programme (grant agreement no.733100).